Desempenho termoenergético de habitação de interesse social - Rios, Gisele Auxiliadora de Almeida [UNESP] (2015)
Energy efficiency actions require interdisciplinary analysis, able to contemplate the complexity expressed by environmental production relations built and habitability. The general purpose of this research was to analyze the impact of the application of bioclimatic strategies in thermoenergy efficiency of social housing (HIS). The research adopted a social housing (HIS) located in Cuiabá / MT as object of study, the methodological steps involved the evaluation of thermal performance and energy efficiency based on the Brazilian normative of three models: standard HIS (HISp), and two more efficient scenarios denominated HISeT (with thermal ink painting on the cover) and HISeTPJ (with paint on the cover and external walls, and windows changed). Through computacional simulation using the EnergyPlus, was obtained projection of the reference consumptions for 13,437 housing built by Minha Casa Minha Vida, in Cuiabá-Várzea Grande (2009-2013). The results show that the model presented better HISeTPJ thermoenergetic performance, enabling energy savings equivalent service over 1.000UC for a period of one year. One of the contributions of this work was to present a system for determining the correlations between changes in internal temperatures and electric power reference consumption, due to interventions in the envelope. It was found a reduction 10,95kWh and 10,85kWh on the electric power consumptions of HISeT and HISeTPJ, when it occurs a 1 ° C decrease in internal temperature of the same. This study interventions in the envelope constitutes innovative proposal and economic viability demonstrated through Cost-Benefit 0.38. It ́s evident the importance of interdisciplinary studies for definition of public policies for energy efficiency and housing